A new model on the use of ubiquitous technology (u-Tech) as a learning tool - Sedek, Muliati; Mahmud, Rosnaini; Ab. Jalil, Habibah; Mohd Daud, Shaffe (Academic World Education & Research Center, 2014)
Laptops, smartphones and tablets which also known as ubiquitous technology or u-tech have been widely used by students in the university. However, study on the factors influencing it usage as not many comprehensive studies have been done related to it. A review of related literature reveals that factors, namely the Technology Competency (TC), Performance Expectancy (PE), Effort Expectancy (EE), Behavioural Intention (BI), Facilitating Conditions (FC) and Social Status (SS) influence its usage. Thus, the focus of this study was to confirm whether the determined factors contribute towards u-tech usage among students in the institutions of higher learning, particularly in Malaysia. This study was based on a quantitative research in which the Structural Equation Modelling using AMOS was employed. The results attained from the analysis produced a reliable model towards u-tech usage. Therefore, it can be concluded that, u-tech usage described by the five factors. This study has suggested that the university administration should play an active role in disseminating any news that is related to the usefulness of u-tech.